1998
DOI: 10.1080/010503998420315
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electrode Position on Near-Threshold Recording of Auditory Evoked Brainstem Potentials

Abstract: Use of brainstem potentials in audiology is based on identifying a response in the near-threshold range. Wave V has turned out to be the component of the brainstem potentials that can be detected with a great deal of reliability when assessment of the threshold for the particular stimulus is desirable. As the detection of Wave I can be dispensed within audiologic diagnosis, the question arises as to whether or not a non-cephalic reference electrode compared to the common lateral position of the reference elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This study set out to investigate whether the effi ciency of auditory brainstem response (ABR) threshold measurement in babies was affected by (i) choice of either high forehead to ipsilateral mastoid or high forehead to nape electrode site, (ii) stimulation rate and (iii) choice of EEG reject level. Pethe et al(1998) reported a larger response when using the nape electrode. The studies by Sininger al (1997Sininger al ( & 2000 give more information related to test effi ciency but have mixed results on choice of electrode site.…”
Section: Ma Fergusonmentioning
confidence: 94%
“…This study set out to investigate whether the effi ciency of auditory brainstem response (ABR) threshold measurement in babies was affected by (i) choice of either high forehead to ipsilateral mastoid or high forehead to nape electrode site, (ii) stimulation rate and (iii) choice of EEG reject level. Pethe et al(1998) reported a larger response when using the nape electrode. The studies by Sininger al (1997Sininger al ( & 2000 give more information related to test effi ciency but have mixed results on choice of electrode site.…”
Section: Ma Fergusonmentioning
confidence: 94%